Pulmonary hypertension in adults with congenital heart disease: real-world data from the international COMPERA-CHD registry - Kaemmerer, Harald; Gorenflo, Matthias; Huscher, Dörte; Pittrow, David; Apitz, Christian; Baumgartner, Helmut; Berger, Felix; Bruch, Leonhard; Brunnemer, Eva; Grünig, Ekkehard; Rosenkranz, Stephan (Journal of Clinical Medicine, 2020)
Introduction: Pulmonary hypertension (PH) is a common complication in patients with congenital heart disease (CHD), aggravating the natural, post-operative, or post-interventional course of the underlying anomaly. The various CHDs differ substantially in characteristics, functionality, and clinical outcomes among each other and compared with other diseases with pulmonary hypertension. Objective: To describe current management strategies and outcomes for adults with PH in relation to different types of CHD based on real-world data. Methods and results: COMPERA (Comparative, Prospective Registry of Newly Initiated Therapies for Pulmonary Hypertension) is a prospective, international PH registry comprising, at the time of data analysis, >8200 patients with various forms of PH. Here, we analyzed a subgroup of 680 patients with PH due to CHD, who were included between 2007 and 2018 in 49 specialized centers for PH and/or CHD located in 11 European countries. At enrollment, the patients’ median age was 44 years (67% female), and patients had either pre-tricuspid shunts, post-tricuspid shunts, complex CHD, congenital left heart or aortic disease, or miscellaneous other types of CHD. Upon inclusion, targeted therapies for pulmonary arterial hypertension (PAH) included endothelin receptor antagonists, PDE-5 inhibitors, prostacyclin analogues, and soluble guanylate cyclase stimulators. Eighty patients with Eisenmenger syndrome were treatment-naïve. While at inclusion the primary PAH treatment for the cohort was monotherapy (70% of patients), with 30% of the patients on combination therapy, after a median observation time of 45.3 months, the number of patients on combination therapy had increased significantly, to 50%. The use of oral anticoagulants or antiplatelets was dependent on the underlying diagnosis or comorbidities. In the entire COMPERA-CHD cohort, after follow-up and receiving targeted PAH therapy (n = 511), 91 patients died over the course of a 5-year follow up. The 5-year Kaplan–Meier survival estimate for CHD associated PH was significantly better than that for idiopathic PAH (76% vs. 54%; p < 0.001). Within the CHD associated PH group, survival estimates differed particularly depending on the underlying diagnosis and treatment status. Conclusions: In COMPERA-CHD, the overall survival of patients with CHD associated PH was dependent on the underlying diagnosis and treatment status, but was significantly better as than that for idiopathic PAH. Nevertheless, overall survival of patients with PAH due to CHD was still markedly reduced compared with survival of patients with other types of CHD, despite an increasing number of patients on PAH-targeted combination therapy.